Da‘wah Strategies for Women’s Empowerment in Grassroots Islamic Organisations: A Case Study in East Java, Indonesia - Yuwafik, Muhammad Hamdan; Nurhikmah, Zizi (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
Despite the growing discourse on women’s empowerment within Islamic da‘wah, empirical studies examining how grassroots Islamic women’s organisations operationalise da‘wah strategies to enhance women’s social, economic, and religious participation remain limited. Existing literature largely focuses on normative or theological discussions, with insufficient attention to practical da‘wah strategies implemented at the local organisational level. Addressing this gap, this study examines the da‘wah strategies employed by the Women’s Wing of Nahdlatul Ulama (Fatayat Nahdlatul Ulama) at the Branch Leadership Council level in Jabung District, Malang Regency, East Java, Indonesia, in strengthening the role of women. This study adopts a qualitative descriptive approach, drawing on the da‘wah strategy framework proposed by Abu al-Fath al-Bayanuni. Data were collected through participant observation, in-depth interviews, and document analysis involving organisational leaders and members. The findings reveal the integration of three interrelated da‘wah strategies. First, sentimental strategies are implemented through spiritual and religious activities such as collective Qur’anic recitation, khatmil Qur’an, istighosah, and Qur’an memorisation circles. Second, rational strategies are enacted through organisational meetings, socialisation programmes, and structured discussions addressing contemporary women’s issues. Third, sensory strategies are realised through entrepreneurship skills training and social service initiatives that directly engage women in productive and communal activities. The novelty of this study lies in its demonstration of how classical da‘wah strategy theory is contextually adapted within a women-led Islamic organisation to create participatory spaces and foster social transformation. The findings contribute to contemporary da‘wah studies by highlighting women’s empowerment as both a strategic objective and a transformative outcome of grassroots Islamic da‘wah practices.